Analysis on the growth of different shapes of mineral microcracks in microwave field - Qin Like; Dai Jun (Fracture and Structural Integrity)
Microwave heating-assisted ore grinding and crushing can effectively increase the dissociation energy of minerals and decrease energy consumption. Microcrack growth and distribution characteristics inside different shapes of ore particles, which are composed of galena and calcite under microwave irradiation, were analyzed using discrete element method to explore the effects of mineral shapes on microwave-assisted dissociation. Growth laws on the total number of microcracks, numbers of microcracks in galena and calcite, and boundary damage rate against irradiation time under high power and low power were studied. Research results demonstrated that mineral shape mainly affects the quantity of microcracks inside ores but does not their growth law.